Pulpitis tendency in teeth with vital pulp restored with composite resins: a cross-sectional retrospective study - Aqili, Tariq M.; Hakeem, Muhannad M.; Almahmadi, Daren S.; Alahmadi, Reem B.; Alsani, Abdulrhman A.; Binmahmoud, Suhail M.; Alotaibi, Waad K.; Mirah, Mahir (International Journal Of Community Medicine And Public Health, 2024)
Background: This study evaluates pulpitis tendency in vital teeth restored with composite resin after at least one year, focusing on the effect of cavity depth and the use of a base material on pulp status. Methods: A retrospective analysis was conducted on 212 patients with one tooth restored by dental senior students. At the follow-up, periapical and bitewing radiographs, cold tests, percussion, and palpation were performed. Cavity depth was measured from bitewing radiographs, and the periapical index (PAI) was recorded. The restored teeth were compared with contralateral sound teeth to assess the impact of the resin on pulp tissue. Results: Composite resin restorations significantly affected pulp status compared to intact teeth (p=0.002). Five out of 212 teeth became necrotic, and four developed symptomatic irreversible pulpitis (SIP). Four necrotic cases occurred in cavities deeper than 3.60 mm, and all SIP cases were associated with cavities deeper than 3.10 mm. Cavity depth was a significant predictor of adverse pulpal outcomes. However, using calcium hydroxide as a base did not significantly affect pulp health. Conclusions: The study concludes that composite resin restorations, mainly in deep cavities, can negatively impact pulp vitality. Cavity depth is a key factor in the risk of pulp necrosis and SIP, while calcium hydroxide base did not reduce pulpitis incidence. Larger studies with longer follow-up periods are recommended to confirm these findings and explore potential protective factors.